1981
DOI: 10.1080/0141192810070105
|View full text |Cite
|
Sign up to set email alerts
|

A Psychological Approach to Research on Teachers' Classroom Decision‐making

Abstract: A number of different approaches to research on teachers' classroom decision‐making have developed over recent years. This paper outlines a psychological approach, and points out that several exploratory studies of teachers' thoughts and decision‐making indicate that, in the classroom, teachers rarely make decisions in the sense of making choices amongst alternatives at all. It would appear instead that they respond in a rule‐fashioned manner to particular configurations of cues, many of which concern attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
5

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 22 publications
2
30
0
5
Order By: Relevance
“…Photographs reflect both their cultural context and at the same time constitute a cultural practice. In contrast to, for example, stimulated recall interviews, where the stimulants are produced and selected by the researcher, here photos act as 'stimulants' that children themselves produce and reflect upon (see also Calderhead, 1981;Cook & Hess, 2007;Smith et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Photographs reflect both their cultural context and at the same time constitute a cultural practice. In contrast to, for example, stimulated recall interviews, where the stimulants are produced and selected by the researcher, here photos act as 'stimulants' that children themselves produce and reflect upon (see also Calderhead, 1981;Cook & Hess, 2007;Smith et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…The notion that teachers make decisions during instructional situations, and adapt instructional actions to meet the individual needs of students has been discussed by many researchers (Borko & Putnam, 1996;Corno, 2008). Early studies in the field, focusing on teacher decision making, found that teachers made decisions in response to classroom management concerns (Calderhead, 1981;Shavelson, 1983) or in response to student cues (Clark & Peterson, 1986). More recently, Nurmi et al, (2013) in their quantitative study with over 300 Finnish first graders explored the extent to which instructional adaptations supported student literacy achievement.…”
Section: Related Literaturementioning
confidence: 98%
“…Ce n'était donc pas une procédure stricte de «rappel stimulé» (Calderhead, 1981;Yinger, 1986). La rétroaction vidéoscopique servait autant à comprendre un contexte qu'à comprendre le développement même de la stagiaire.…”
Section: Devis De La Rechercheunclassified